ANALISIS FRAMEWORK COBIT 5.0 PADA APLIKASI LARK SUITE SEBAGAI PLATFORM KOLABORASI MENINGKATKAN KINERJA TIM DI PT WEEFER INDONESIA - Vincent Z; Erlin Elisa (Computer Science and Industrial Engineering, 2024)
The rapid advancement of technology is driving digital transformation across various sectors of life, including the business world. PT Weefer Indonesia, as a company focusing on digital transformation, plays a crucial role in the effective implementation of information technology. Particularly since the Covid-19 pandemic, the company has adopted a hybrid work model with the support of the Lark Suite application. Lark Suite serves as a team collaboration tool, providing a messaging platform, video conferencing, and a calendar to facilitate internal and external communication. This research aims to measure the maturity level of the Lark Suite application during its usage at PT Weefer Indonesia using the COBIT 5.0 framework. COBIT 5.0, as a comprehensive management guide, provides a foundation for analyzing system performance. Based on previous research conducted by other scholars using the COBIT 5.0 framework, its effectiveness in identifying the maturity level of information systems has been proven. The use of COBIT 5 is expected to provide in-depth insights into the maturity level of the application and identify areas that can be enhanced or developed to improve the efficiency and effectiveness of team collaboration. This research is anticipated to contribute positively to the company in understanding and enhancing the utilization of the adopted collaboration application.